Porous adsorption resin purified by silane and preparation method of porous adsorption resin

By combining the modified mesoporous magnetic particles with acrylic resin, a porous adsorption resin with efficient removal of silane impurities was prepared, which solved the problems of insufficient silane purity and poor adsorption stability in the prior art, and achieved high purity and low cost silane Purification effect.

CN119264345APending Publication Date: 2025-01-07CHENGDU ZHICHENG DAGONG PHOTOELECTRIC TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411466941.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing silane preparation methods have problems such as high cost, many by-products, high energy consumption, unstable product quality and impurities residues. It is especially difficult to efficiently remove chloride ions and metal impurities, resulting in insufficient purity of silane to meet the needs of high-end applications.

Method used

Modified mesoporous magnetic particles combined with acrylic resin to prepare porous adsorption resin through specific preparation steps. The mesoporous structure and group modification are used to improve adsorption capacity, forming a resin with a high specific surface area and appropriate pore size distribution, which can efficiently remove silanes. impurities in it.

Benefits of technology

The purity of silane products has been significantly improved to reach 99.998% or above, maintaining good adsorption stability and selectivity, reducing the frequency of adsorbent replacement, reducing operating costs, and meeting the purity requirements of high-end applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264345A_ABST
    Figure CN119264345A_ABST
Patent Text Reader

Abstract

The invention discloses porous adsorption resin for silane purification and a preparation method of the porous adsorption resin, and belongs to the technical field of silane production. The porous adsorption resin is prepared from the following components in parts by weight: 100 to 200 parts of deionized water, 10 to 30 parts of modified mesoporous magnetic particles, 20 to 40 parts of acrylic resin monomer, 5 to 15 parts of N, N-methylene bisacrylamide, 10 to 20 parts of polypropylene glycol monomethyl ether acrylate and 20 to 50 parts of initiator aqueous solution. The prepared porous adsorption resin can efficiently remove chloride ions and metal impurities in silane, the purity of a silane product is improved, the product purity can reach 99.998% or above, the requirement for the purity of silane in the high-end application field is met, good adsorption stability is achieved, bonding between the adsorption resin and the silane impurities is firmer, and the service life of the adsorption resin is prolonged. According to the present invention, the high adsorption capacity can be maintained after the multi-time cycle use, such that the purification precision and the purification effect are improved due to the appropriate pore size distribution, the selectivity on the impurity adsorption is provided, and the targeted adsorption can be performed according to the size and the property of the impurity molecule.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of silane production, and in particular relates to a porous adsorption resin for silane purification and a preparation method thereof. Background Art

[0002] Tetraethoxysilane is an important organosilicon compound with a wide range of applications. In the semiconductor field, it can be used to prepare precursors for silicon-based semiconductor materials. Through chemical vapor deposition and other methods, a silicon dioxide insulation layer or other silicon-containing film is formed on the surface of semiconductor chips to improve the performance and reliability of semiconductor devices. In terms of electrical insulation materials, due to its good insulation performance and chemical stability, it is used in wire and cable insulation coatings, electronic component packaging materials, etc., to ensure the safety and service life of electrical equipment. In the field of coatings, it can be used as an additive to enhance the adhesion, water resistance, corrosion resistance and wear resistance of coatings, and improve the quality and life of coatings. For example, in architectural coatings, it can make the coating adhere better to the surface of the building and improve waterproofness and durability. In optical glass processing, it is used to improve the optical, mechanical and chemical properties of optical glass. For example, forming a silicon dioxide film on its surface can improve hardness, scratch resistance and UV resistance. It can also be used as an organic synthesis intermediate to synthesize other organosilicon compounds and functional materials, and to prepare organosilicon polymers with special properties for material modification and functionalization.

[0003] Traditional preparation methods of tetraethoxysilane include silicon tetrachloride method and silicon powder method: silicon tetrachloride method has high raw material cost, many by-products, long production cycle, low output, high energy consumption, unstable product quality and serious environmental pollution. Because silicon tetrachloride is toxic and corrosive, the production process requires strict safety protection and the cost of by-product treatment is high; although the silicon powder method can avoid some disadvantages, it cannot avoid the process of high-temperature reduction of silicon dioxide to prepare elemental silicon, which has problems such as large catalyst dosage, high energy consumption, poor reaction stability and safety hazards caused by the large amount of hydrogen produced by the reaction. In tetraethoxysilane products, there are often impurities containing chloride ions, and the presence of metal impurities will also seriously affect the quality and performance of tetraethoxysilane. However, some existing purification technologies often cannot efficiently remove various impurities in silane, especially chloride ions and metal impurities. The residues of these impurities will reduce the purity of silane products and it is difficult to meet the strict requirements of silane purity in high-end application fields. In addition, the existing adsorbents perform poorly in terms of adsorption stability. After repeated cycles, the adsorption capacity will drop significantly, resulting in an increase in the frequency of adsorbent replacement and an increase in operating costs. Therefore, it is of great practical significance to develop a porous adsorption resin and a preparation method thereof that can efficiently remove silane impurities, improve product purity and have good adsorption stability. Summary of the invention

[0004] In view of the above situation, in order to overcome the defects of the prior art, the present invention realizes the preparation of a porous adsorption resin for silane purification and its application in the efficient removal of silane impurities through specific components and preparation processes, significantly improves the purity of the silane product and has multiple excellent properties such as good adsorption stability.

[0005] In order to achieve the above object, the following technical scheme is adopted: On the one hand, the present invention provides a porous adsorption resin purified by silane, comprising the following components in parts by weight:

[0006] 100-200 parts of deionized water, 10-30 parts of modified mesoporous magnetic particles, 20-40 parts of acrylic resin monomer, 5-15 parts of N,N-methylenebisacrylamide, 10-20 parts of polypropylene glycol monomethyl ether acrylate, and 20-50 parts of initiator aqueous solution.

[0007] Furthermore, the modified mesoporous magnetic particles are prepared by the following steps:

[0008] (1) FeCl 3 and FeCl 2 Mix with ethylenediaminetetraacetic acid, polydimethyldiallylammonium chloride and deionized water under nitrogen protection, quickly add 25% ammonia water by mass when the temperature rises to 50°C, then keep the temperature to react for 5 hours, filter, adsorb with a magnet, wash and dry to obtain mesoporous magnetic particles;

[0009] (2) adding 2-vinyl-4,4-dimethyl-2-oxazolin-5-one to a mixed solution of ethanol and water in a volume ratio of 1:1, adding 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane under nitrogen protection, then heating to 60° C., adding the mesoporous magnetic particles, reacting for 5 hours, then filtering, washing with deionized water, and drying to obtain oxazolinone-modified mesoporous magnetic particles;

[0010] (3) Deionized water, oxazolinone-modified mesoporous magnetic particles and 3-aminopyrazine-2-carboxylic acid methyl ester are mixed under nitrogen protection, and then the temperature is raised to react for 5 hours, and then filtered, washed with ethanol and deionized water, and dried to obtain the modified mesoporous magnetic particles.

[0011] The present invention first prepares Fe with a mesoporous structure 3 O 4 The mesoporous magnetic particles are prepared by reacting 2-vinyl-4.4-dimethyl-2-oxazolin-5-one with a hydrolyzed 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane coupling agent to introduce an oxazolinone group into the coupling agent, and then modifying the mesoporous magnetic particles with the coupling agent. Finally, the modified mesoporous magnetic particles are combined with 3-aminopyrazine-2-carboxylic acid methyl ester through epoxy ring opening of the coupling agent to obtain modified mesoporous magnetic particles.

[0012] Furthermore, in step (1), FeCl 3 、FeCl 2 The mass ratio of ethylenediaminetetraacetic acid, polydimethyldiallylammonium chloride and deionized water is 2-3:1:3-5:0.3-0.5:60-80.

[0013] Furthermore, the mass of the ammonia water in step (1) is FeCl 3 and FeCl 2 3-5 times the quality.

[0014] Furthermore, in the step (2), the mass ratio of 2-vinyl-4.4-dimethyl-2-oxazolin-5-one, the mixed solution of anhydrous ethanol and water, 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane and the mesoporous magnetic particles is 1:1-3:2-4:5-10.

[0015] Furthermore, in the step (3), the mass ratio of deionized water, oxazolinone-modified mesoporous magnetic particles and 3-aminopyrazine-2-carboxylic acid methyl ester is 5-8:1.5-3:1.

[0016] Furthermore, the initiator aqueous solution comprises the following components in parts by weight: 5-10 parts of sodium persulfate, 3-8 parts of sodium bisulfite and 50-100 parts of deionized water.

[0017] Furthermore, the acrylic monomer is one of ethyl acrylate, butyl acrylate, methyl methacrylate and hydroxyethyl acrylate.

[0018] On the other hand, the present invention also provides a method for preparing a porous adsorption resin purified by silane, comprising the following steps: adding the modified mesoporous magnetic particles into deionized water, then adding acrylic resin monomer and N,N-methylenebisacrylamide under nitrogen protection, adding polypropylene glycol monomethyl ether acrylate after high-speed shearing until uniform, heating to 60°C, then dripping an initiator aqueous solution, maintaining a constant temperature of 60°C for reaction for 5 hours, cooling, washing three times with anhydrous ethanol and deionized water, crushing, and drying to obtain the porous adsorption resin.

[0019] Furthermore, the rotation speed of the high-speed shearing is 3000-5000 rpm, and the time is 20-50 min.

[0020] The beneficial effects of the present invention are:

[0021] (1) The adsorption resin prepared by the present invention can efficiently remove impurities in silane, including chloride ions and metal impurities, and significantly improve the purity of silane products. The product purity can reach 99.998% or above, meeting the strict requirements of high-end application fields for silane purity, and has good adsorption stability. Through special group modification and structural design, the combination between the adsorption resin and silane impurities is made stronger, and a high adsorption capacity can be maintained after multiple cycles of use, reducing the frequency of adsorbent replacement and reducing operating costs. Thanks to the appropriate pore size distribution, the purification accuracy and effect are improved, the adsorption of impurities is selective, and targeted adsorption can be performed according to the size and properties of impurity molecules;

[0022] (2) The present invention first prepares magnetic particles with a mesoporous structure, wherein polydimethyldiallylammonium chloride serves as a surfactant to reduce the surface tension and surface free energy of the generated nanoparticles and regulate the particle size, and can also regulate the surface charge of the mesoporous magnetic particles and improve the dispersibility of the particles. The obtained particle size is nanometer-level, and impurities can be transported in the pores and easily reach the active sites in the pores to be captured and removed by the internal active sites, and the adsorption rate is faster. The magnetic nanoparticles are then modified by the oxazolidinone structure. The oxazolidinone group can not only form multiple interactions such as hydrogen bonding and π-π stacking with silane impurity molecules, but also form a tighter bond with the silane impurity molecules through electron cloud distribution and spatial configuration, further enhancing the affinity of the adsorption resin for silane impurities, greatly improving the capture and adsorption efficiency of the resin for various impurity molecules in silane, thereby significantly improving the purity of the silane product;

[0023] (3) The present invention utilizes 3-aminopyrazine-2-carboxylic acid methyl ester to modify the nanoparticles. The amino group in the aminopyrazine group has strong basicity and nucleophilicity, and can react chemically or electrostatically with the acidic or polarizable groups in the silane impurities, thereby being able to more firmly bind to the silane impurities, thereby increasing the adsorption stability and capacity, and maintaining a high adsorption performance after multiple cycles of use;

[0024] (4) The modified magnetic nanoparticles form longer cross-linked bridges during the preparation of the resin, which can form a larger spatial network structure inside the resin, which is beneficial to the transmission and diffusion of substances. At the same time, the pore structure and specific surface area of ​​the resin can be adjusted, so that the adsorption resin has a high specific surface area while maintaining a suitable pore size distribution, further improving the adsorption performance and selectivity of silane impurities and increasing the adsorption capacity of metal impurities. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The durability test results of the porous adsorption resins of Example 3, Comparative Example 1 and Comparative Example 2 of the present invention are shown.

[0026] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0028] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.

[0029] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.

[0030] Example 1

[0031] A kind of porous adsorption resin purified by silane and preparation method thereof

[0032] The porous adsorption resin comprises the following components in parts by weight:

[0033] 100 parts of deionized water, 10 parts of modified mesoporous magnetic particles, 20 parts of acrylic resin monomer, 5 parts of N,N-methylenebisacrylamide, 10 parts of polypropylene glycol monomethyl ether acrylate, and 20 parts of initiator aqueous solution.

[0034] The modified mesoporous magnetic particles are prepared by the following steps:

[0035] (1) FeCl 3 and FeCl 2 Mix with ethylenediaminetetraacetic acid, polydimethyldiallylammonium chloride and deionized water under nitrogen protection, quickly add 25% ammonia water by mass when the temperature rises to 50°C, then keep the temperature to react for 5 hours, filter, adsorb with a magnet, wash and dry to obtain mesoporous magnetic particles;

[0036] (2) adding 2-vinyl-4,4-dimethyl-2-oxazolin-5-one to a mixed solution of ethanol and water in a volume ratio of 1:1, adding 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane under nitrogen protection, then heating to 60° C., adding the mesoporous magnetic particles, reacting for 5 hours, then filtering, washing with deionized water, and drying to obtain oxazolinone-modified mesoporous magnetic particles;

[0037] (3) Deionized water, oxazolinone-modified mesoporous magnetic particles and 3-aminopyrazine-2-carboxylic acid methyl ester are mixed under nitrogen protection, and then the temperature is raised to react for 5 hours, and then filtered, washed with ethanol and deionized water, and dried to obtain the modified mesoporous magnetic particles.

[0038] In the step (1), FeCl 3 、FeCl 2 The mass ratio of ethylenediaminetetraacetic acid, polydimethyldiallylammonium chloride and deionized water is 2:1:3:0.3:60.

[0039] The mass of ammonia water in step (1) is FeCl 3 and FeCl 2 3 times the quality.

[0040] In the step (2), the mass ratio of 2-vinyl-4.4-dimethyl-2-oxazolin-5-one, the mixed solution of anhydrous ethanol and water, 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane and the mesoporous magnetic particles is 1:1:2:5.

[0041] In the step (3), the mass ratio of deionized water, oxazolinone-modified mesoporous magnetic particles and 3-aminopyrazine-2-carboxylic acid methyl ester is 5:1.5:1.

[0042] The initiator aqueous solution comprises the following components in parts by weight: 5 parts of sodium persulfate, 3 parts of sodium bisulfite and 50-100 parts of deionized water.

[0043] The acrylic acid monomer is ethyl acrylate.

[0044] The preparation method of the porous adsorption resin comprises the following steps: adding the modified mesoporous magnetic particles into deionized water, then adding acrylic resin monomer and N,N-methylenebisacrylamide under nitrogen protection, adding polypropylene glycol monomethyl ether acrylate after high-speed shearing until uniform, heating to 60°C, then dripping an initiator aqueous solution, maintaining a constant temperature of 60°C for reaction for 5 hours, cooling, washing three times with anhydrous ethanol and deionized water, crushing, and drying to obtain the porous adsorption resin.

[0045] The high-speed shearing speed is 3000 rpm and the time is 20 min.

[0046] Example 2

[0047] A kind of porous adsorption resin purified by silane and preparation method thereof

[0048] The porous adsorption resin comprises the following components in parts by weight:

[0049] 200 parts of deionized water, 30 parts of modified mesoporous magnetic particles, 40 parts of acrylic resin monomer, 15 parts of N,N-methylenebisacrylamide, 20 parts of polypropylene glycol monomethyl ether acrylate, and 50 parts of initiator aqueous solution.

[0050] The preparation steps of the modified mesoporous magnetic particles are the same as those in Example 1.

[0051] In the step (1), FeCl 3 、FeCl 2 The mass ratio of ethylenediaminetetraacetic acid, polydimethyldiallylammonium chloride and deionized water is 3:1:5:0.5:80.

[0052] The mass of ammonia water in step (1) is FeCl 3 and FeCl 2 5 times the quality.

[0053] In the step (2), the mass ratio of 2-vinyl-4.4-dimethyl-2-oxazolin-5-one, the mixed solution of anhydrous ethanol and water, 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane and the mesoporous magnetic particles is 1:3:4:10.

[0054] In the step (3), the mass ratio of deionized water, oxazolinone-modified mesoporous magnetic particles and 3-aminopyrazine-2-carboxylic acid methyl ester is 8:3:1.

[0055] The initiator aqueous solution includes the following components in parts by weight: 10 parts of sodium persulfate, 8 parts of sodium bisulfite and 100 parts of deionized water.

[0056] The acrylic acid monomer is butyl acrylate.

[0057] The preparation method of the porous adsorption resin is the same as that in Example 1.

[0058] The high-speed shearing has a rotation speed of 5000 rpm and a time of 50 min.

[0059] Example 3

[0060] A kind of porous adsorption resin purified by silane and preparation method thereof

[0061] The porous adsorption resin comprises the following components in parts by weight:

[0062] 160 parts of deionized water, 25 parts of modified mesoporous magnetic particles, 30 parts of acrylic resin monomer, 10 parts of N,N-methylenebisacrylamide, 15 parts of polypropylene glycol monomethyl ether acrylate, and 30 parts of initiator aqueous solution.

[0063] The preparation steps of the modified mesoporous magnetic particles are the same as those in Example 1.

[0064] In the step (1), FeCl 3 、FeCl 2 The mass ratio of ethylenediaminetetraacetic acid, polydimethyldiallylammonium chloride and deionized water is 2.5:1:3.5:0.4:70.

[0065] The mass of ammonia water in step (1) is FeCl 3 and FeCl 2 4 times the quality.

[0066] In the step (2), the mass ratio of 2-vinyl-4.4-dimethyl-2-oxazolin-5-one, the mixed solution of anhydrous ethanol and water, 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane and the mesoporous magnetic particles is 1:2:2.5:7.

[0067] In the step (3), the mass ratio of deionized water, oxazolinone-modified mesoporous magnetic particles and 3-aminopyrazine-2-carboxylic acid methyl ester is 7:2:1.

[0068] The initiator aqueous solution includes the following components in parts by weight: 6 parts of sodium persulfate, 5 parts of sodium bisulfite and 60 parts of deionized water.

[0069] The acrylic acid monomer is methyl methacrylate.

[0070] The preparation method of the porous adsorption resin is the same as that in Example 1.

[0071] The high-speed shearing speed is 4000 rpm and the time is 40 minutes.

[0072] Example 4

[0073] A kind of porous adsorption resin purified by silane and preparation method thereof

[0074] The porous adsorption resin in this embodiment includes the following components in parts by weight:

[0075] 160 parts of deionized water, 30 parts of modified mesoporous magnetic particles, 20 parts of acrylic resin monomer, 10 parts of N,N-methylenebisacrylamide, 10 parts of polypropylene glycol monomethyl ether acrylate, and 20 parts of initiator aqueous solution.

[0076] The rest is the same as Example 3.

[0077] Example 5

[0078] A kind of porous adsorption resin purified by silane and preparation method thereof

[0079] In this embodiment, the acrylic acid monomer is hydroxyethyl acrylate, and the rest is the same as in Embodiment 3.

[0080] Comparative Example 1

[0081] In this comparative example, the mesoporous magnetic particles obtained in step (1) are used instead of the mesoporous magnetic particles modified with oxazolidinone, and the rest are the same as those in Example 3.

[0082] Comparative Example 2

[0083] In this comparative example, no 3-aminopyrazine-2-carboxylic acid methyl ester was added in step (3), and the rest was the same as in Example 3.

[0084] Comparative Example 3

[0085] The modified mesoporous magnetic particles described in this comparative example are prepared by the following steps:

[0086] (1) FeCl 3 and FeCl 2 When the temperature is raised to 50°C under nitrogen protection, 25% ammonia water is quickly added, and then the mixture is kept warm for 5 hours, filtered, adsorbed with a magnet, washed, and dried to obtain mesoporous magnetic particles;

[0087] (2) adding 2-vinyl-4,4-dimethyl-2-oxazolin-5-one to a mixed solution of ethanol and water in a volume ratio of 1:1, adding 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane under nitrogen protection, then heating to 60° C., adding the mesoporous magnetic particles, reacting for 5 hours, then filtering, washing with deionized water, and drying to obtain oxazolinone-modified mesoporous magnetic particles;

[0088] (3) Deionized water, oxazolinone-modified mesoporous magnetic particles and 3-aminopyrazine-2-carboxylic acid methyl ester are mixed under nitrogen protection, and then the temperature is raised to react for 5 hours, and then filtered, washed with ethanol and deionized water, and dried to obtain the modified mesoporous magnetic particles.

[0089] The rest is the same as Example 3.

[0090] Test Example 1

[0091] Porous adsorption resin performance test

[0092] The specific surface area and average porosity of the porous adsorption resin prepared in each embodiment and comparative example were tested by a fully automatic BET specific surface area analysis tester, and the water content of the porous adsorption resin prepared in each embodiment and comparative example was determined with reference to the water content determination method of ion exchange resin in GB / T 5757-2008.

[0093] Table 1 Test results of porous adsorption resin performance

[0094]

[0095] It can be seen from the table that the performance indicators of the porous adsorption resins synthesized in the four embodiments of the present invention are better than those of the commercially available porous adsorption resins, and have a moderate water content. The specific surface areas of the porous adsorption resins synthesized in the four embodiments of the present invention are between 1208 and 1280 m 2 / g, the average pore size is The water content is between 60.3% and 63.5%, while the specific surface area of ​​comparative examples 1 and 2 is relatively low, the average pore size is larger, and the water content is similar to that of the embodiment; it proves that the present invention prepares mesoporous magnetic nanoparticles by ethylenediaminetetraacetic acid, polydimethyldiallylammonium chloride and ammonia water, modifies the magnetic nanoparticles by oxazolidinone structure, and modifies the nanoparticles by 3-aminopyrazine-2-carboxylic acid methyl ester, and the modified magnetic nanoparticles form longer cross-linked bridges when preparing the resin, and form a larger spatial network structure inside the resin, which is beneficial to the transmission and diffusion of substances, and can adjust the pore structure and specific surface area of ​​the resin at the same time, which explains why the porous adsorption resin in the embodiment has a higher specific surface area and a suitable pore size distribution, while the comparative example may have a lower specific surface area and a larger pore size due to the lack of effective modification.

[0096] Test Example 2

[0097] Porous adsorption resin durability test

[0098] The porous adsorption resins prepared in Example 3, Comparative Example 1 and Comparative Example 2 were subjected to 6 cycles of adsorption and desorption. The relationship between the adsorption capacity of the resin and the number of cycles is shown in FIG. Figure 1 shown.

[0099] from Figure 1It can be seen that the adsorption resin of the present invention has good adsorption stability. Through special group modification and structural design, the binding between the adsorption resin and the silane impurities is made stronger, and a high adsorption capacity can be maintained after multiple cycles of use. For example, the porous adsorption resin prepared in Example 3 still has a high adsorption capacity for impurities after 6 adsorption-desorption cycles, and has good repeatability. This is because the magnetic particles with a mesoporous structure prepared by the present invention have improved particle dispersibility, prevent particle agglomeration, and form a variety of interactions between the oxazolidinone group and the silane impurity molecules, such as hydrogen bonding, π-π stacking, etc., which enhances the affinity of the adsorption resin for silane impurities, so that the resin can more effectively capture and adsorb impurity molecules and metal impurities in silane. At the same time, the amino group in the aminopyrazine group has strong alkalinity and nucleophilicity, and can react chemically or electrostatically with the acidic or polarizable groups in the silane impurities, thereby increasing the adsorption stability and capacity. These effects enable the adsorption resin to maintain a high adsorption performance after multiple cycles of use, while Comparative Examples 1 and 2 may lack these effective modifications, resulting in a rapid decrease in adsorption capacity after multiple cycles of use.

[0100] Test Example 3

[0101] Tetraethoxysilane purity test

[0102] After the porous adsorption resin prepared in each embodiment and comparative example adsorbs tetraethoxysilane, the tetraethoxysilane product is subjected to a purity test to measure the product purity, chloride ion content and metal impurity content.

[0103] As shown in Table 2, the removal efficiency of tetraethoxysilane in each embodiment of the present invention is high, and the content of chloride ions and metal impurities is greatly reduced, so the purity of the tetraethoxysilane product is high. The removal efficiency of tetraethoxysilane in each embodiment of the present invention is high, and the content of chloride ions and metal impurities is greatly reduced. The product purity is between 99.998% and 99.999%, while the product purity of Comparative Examples 1 and 2 is relatively low, and the content of chloride ions and metal impurities is high. The mesoporous nanoparticles prepared by the present invention, and the modification of the magnetic nanoparticles by the oxazolidinone structure and the modification of 3-aminopyrazine-2-carboxylic acid methyl ester enhance the affinity of the adsorption resin for silane impurities, and can more effectively capture and adsorb impurity molecules and metal impurities in silane, thereby improving the purity of tetraethoxysilane. In the comparative example, due to the lack of effective modification, the adsorption capacity for impurities is weak, resulting in a low product purity.

[0104] Table 2 Tetraethoxysilane purity test results

[0105] project Product purity / % Chloride ion content / ppm Metal impurity content / ppm Example 1 99.998 6.5 9.5 Example 2 99.999 5.2 6.0 Example 3 99.999 4.5 7.2 Example 4 99.998 8.6 9.7 Example 5 99.998 8.5 10.1 Comparative Example 1 99.995 24.5 22.8 Comparative Example 2 99.993 34.7 35.5 Comparative Example 3 99.992 45.5 42.2

[0106] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

[0107] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A porous adsorption resin purified by silane, characterized in that: The composition comprises the following components in parts by weight: 100-200 parts of deionized water, 10-30 parts of modified mesoporous magnetic particles, 20-40 parts of acrylic resin monomer, 5-15 parts of N,N-methylenebisacrylamide, 10-20 parts of polypropylene glycol monomethyl ether acrylate, and 20-50 parts of initiator aqueous solution; The modified mesoporous magnetic particles are prepared by the following steps: (1) FeCl3 and FeCl2 are mixed with ethylenediaminetetraacetic acid, polydimethyldiallylammonium chloride and deionized water under nitrogen protection, and when the temperature is raised to 50°C, 25% ammonia water is quickly added, and then the mixture is kept warm for 5 hours, filtered, adsorbed with a magnet, washed, and dried to obtain mesoporous magnetic particles; (2) adding 2-vinyl-4,4-dimethyl-2-oxazolin-5-one to a mixed solution of ethanol and water in a volume ratio of 1:1, adding 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane under nitrogen protection, then heating to 60° C., adding the mesoporous magnetic particles, reacting for 5 hours, then filtering, washing with deionized water, and drying to obtain oxazolinone-modified mesoporous magnetic particles; (3) Deionized water, oxazolinone-modified mesoporous magnetic particles and 3-aminopyrazine-2-carboxylic acid methyl ester are mixed under nitrogen protection, and then the temperature is raised to react for 5 hours, and then filtered, washed with ethanol and deionized water, and dried to obtain the modified mesoporous magnetic particles.

2. The porous adsorption resin purified by silane according to claim 1, characterized in that: In the step (1), the mass ratio of FeCl3, FeCl2, ethylenediaminetetraacetic acid, polydimethyldiallylammonium chloride and deionized water is 2-3:1:3-5:0.3-0.5:60-80.

3. The porous adsorption resin purified by silane according to claim 2, characterized in that: The mass of the ammonia water in step (1) is 3-5 times the mass of FeCl3 and FeCl2.

4. The porous adsorption resin purified by silane according to claim 3, characterized in that: In the step (2), the mass ratio of 2-vinyl-4.4-dimethyl-2-oxazolin-5-one, the mixed solution of anhydrous ethanol and water, 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane and the mesoporous magnetic particles is 1:1-3:2-4:5-10.

5. The porous adsorption resin purified by silane according to claim 4, characterized in that: In the step (3), the mass ratio of deionized water, oxazolinone-modified mesoporous magnetic particles and 3-aminopyrazine-2-carboxylic acid methyl ester is 5-8:1.5-3:

1.

6. The porous adsorption resin purified by silane according to claim 5, characterized in that: The initiator aqueous solution comprises the following components in parts by weight: 5-10 parts of sodium persulfate, 3-8 parts of sodium bisulfite and 50-100 parts of deionized water.

7. The porous adsorption resin purified by silane according to claim 6, characterized in that: The acrylic acid monomer is one of ethyl acrylate, butyl acrylate, methyl methacrylate and hydroxyethyl acrylate.

8. A method for preparing a porous adsorption resin purified by silane according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: adding the modified mesoporous magnetic particles into deionized water, then adding acrylic resin monomer and N,N-methylenebisacrylamide under nitrogen protection, adding polypropylene glycol monomethyl ether acrylate after high-speed shearing until uniform, heating to 60°C, then dripping an initiator aqueous solution, maintaining a constant temperature of 60°C for reaction for 5 hours, cooling, washing with anhydrous ethanol and deionized water three times, crushing, and drying to obtain the porous adsorption resin.

9. The method for preparing a porous adsorption resin purified by silane according to claim 8, characterized in that: The high-speed shearing speed is 3000-5000 rpm, and the time is 20-50 min.